SPE Annual Technical Conference and Exhibition 2016
DOI: 10.2118/181361-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in Openhole Sand Control Applications Using Shape Memory Polymer

Abstract: This paper summarizes a game-changing technology using shape memory polymer (SMP) to provide downhole sand control in openhole environments. An openhole completion maximizes well productivity/injectivity and longevity without the concern of plugging and/or collapsing perforation tunnels that are frequent challenges in cased-hole completions. Conventional openhole sand control techniques include stand-alone-screen (SAS), expandable screens and openhole gravel packing (OHGP). In some cases, the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Many researchers [33][34][35][36][37][38][39][40][41][42][43] find a notably high influence of fine fractions (<50 µm) on the well operation (mainly plugging screens), as a result, the material associated with the formation of sand arches was worked out, but significant results were not achieved in by analyzing the literature (except for the connection of the aforementioned arches with the process of the natural decrease in the number of suspended particles in the first few days of well operation).…”
Section: Geomechanical Modelingmentioning
confidence: 99%
“…Many researchers [33][34][35][36][37][38][39][40][41][42][43] find a notably high influence of fine fractions (<50 µm) on the well operation (mainly plugging screens), as a result, the material associated with the formation of sand arches was worked out, but significant results were not achieved in by analyzing the literature (except for the connection of the aforementioned arches with the process of the natural decrease in the number of suspended particles in the first few days of well operation).…”
Section: Geomechanical Modelingmentioning
confidence: 99%
“…This material can be used to permit all particles less than 43 microns to flow easily through the filter screen and stop the sand particles greater than 43 microns to control sand production. Carrejo et al [25], Wang et al [90], Leung et al [91], and Fuxa et al [92] used shape memory polymers to control the sand formation, (See Table 13). The used shape memory polymers have shown permeability ranges from 5 to 600 mD at temperature of 37.8-93.3 • C [25,91,92].…”
Section: Shape Memory Polymersmentioning
confidence: 99%
“…SMPs also have a variety of applications in petroleum engineering. Thermally actuated SMPs are the most commonly used materials, for example, intelligent plugging drilling fluids [ 9 ], self-expanding cement [ 10 , 11 ], intelligent sand control technology [ 12 , 13 ], etc. Field tests and laboratory studies have demonstrated that technologies involving SMPs have significantly improved oil recovery rates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%